Hosea 4 and 11, and the structure of Hosea - Goldingay, John (Tyndale bulletin, 2021)
Hosea 4:1-3 pronounces an indictment on the entire world as a way of getting home a message to Ephraim. It opens a series of biddings in 4:1–9:9 that seek to get Ephraim to face the facts about itself and about the danger it is in. Hosea 9:10–13:16 [14:1] then comprises a series of reminders of past and present realities in the relationship between Israel and Yahweh. Within it, 11:1-11 is not a self-contained pericope marking mercy’s final victory over wrath, but part of 11:1–12:1 [2], which continues to urge Ephraim to choose between doom and hope.